2005
DOI: 10.1089/clo.2005.7.238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nuclear-Donor Cell Lineage, Type, and Cell Donor on Development of Somatic Cell Nuclear Transfer Embryos in Cattle

Abstract: Potential applications of somatic cell nuclear transfer to agriculture and medicine are currently constrained by low efficiency and high rates of embryonic, fetal, and neonatal loss. Nuclear transfer efficiency in cattle was compared between three donor-cell treatments from a single animal, between four donor-cell treatments in sequential stages of differentiation from a single cell lineage and genotype, and between the same cell type in two donors. Cumulus and granulosa donor cells resulted in a greater propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
14

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 57 publications
0
14
0
14
Order By: Relevance
“…Cloned calves from adult somatic cell nuclear transfer (Holstein, n Ï­ 5; Hereford, n Ï­ 3) and ET control calves (Holstein, n Ï­ 3; Hereford, n Ï­ 3) were produced as previously described, according to our established procedures (Batchelder et al, 2005). Briefly, nuclear-transfer experiments were conducted with donor cells from ear skin, cumulus, and granulosa cell lines from a 13-yearold Hereford donor and with donor cells from preantral follicle, cumulus, granulosa, and luteal cell lines from a 3-year-old Holstein donor.…”
Section: Animalsmentioning
confidence: 99%
“…Cloned calves from adult somatic cell nuclear transfer (Holstein, n Ï­ 5; Hereford, n Ï­ 3) and ET control calves (Holstein, n Ï­ 3; Hereford, n Ï­ 3) were produced as previously described, according to our established procedures (Batchelder et al, 2005). Briefly, nuclear-transfer experiments were conducted with donor cells from ear skin, cumulus, and granulosa cell lines from a 13-yearold Hereford donor and with donor cells from preantral follicle, cumulus, granulosa, and luteal cell lines from a 3-year-old Holstein donor.…”
Section: Animalsmentioning
confidence: 99%
“…The high rate of pregnancy failure in recipients of cloned embryos has been linked to the finding of structural and functional abnormalities of the placenta. Losses of pregnancy in surrogate dams in the second and third trimester are associated with placental abnormalities, hydrops, enlarged umbilical cords with dilated vessels, and abnormally enlarged and fewer placental cotyledons (11)(12)(13). This abnormal placental development may be present from the early stages after implantation and can be overcome by some embryos that result in the development and birth of live clones (12,14,15).…”
mentioning
confidence: 99%
“…Yang et al [5] found that CCs and FFs have the same potential to support development of cloned rabbit embryos to the blastocyst stage. In contrast, many reports on cattle have suggested that CCs appear to be the best choice because of the highest cloning efficiency among the cells examined [12,15,18,25,[33][34][35]. Also, in buffalos, Shah et al [19] produced cloned embryos by a handmade cloning (HMC) technique and found that the blastocyst formation rate of embryos derived from CCs was better than those of embryos derived from FFs or adult fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the reported cloning efficiency for each donor cell type is difficult due to variations in the nuclear-transfer procedures, source and quality of recipient oocytes, age and genotype of the donor cells and embryo culture systems used in the studies [18]. Furthermore, there have been few reports about the effect of donor cell types on the developmental potential of cloned buffalo embryos [4,19].…”
mentioning
confidence: 99%